Fracture Resistance of Porcelain Laminate Veneers - KAHRAMANOĞLU, ERKUT; ÖZKAN, YASEMİN; ASLAN, YILMAZ UMUT (AVES PRESS LTD, 2018)
In recent dentistry, laminate veneers have gained widespread utilization as a conservative treatment option of unaesthetic anterior teeth. The continued development of dental ceramics offers clinicians many options for creating highly aesthetic and functional porcelain veneers. The behavior of these restorations against the functional loads plays an important role in their success. Many studies have evaluated the fracture resistance of laminate veneers in vitro and in vivo.
Keywords: Esthetic; laminate veneer; fracture resistance; OF-THE-LITERATURE; LITHIUM DISILICATE; CERAMIC VENEERS; CEMENT LUTE; STRENGTH; CROWNS; INCISORS